The Optimal Distribution of Cooling Elements - Račkienė, R.; Virbalis, J. A.; Bartkevičius, S.; Lukočius, R. (Elektronika ir Elektrotechnika, 2010)
The efficiency of the cooling system depends on the choice of the cooling elements. There is important to consider to thermoelectric parameters, the size, distribution and the price of the elements. There is analyzed the process of the calculation of Peltier elements, presented the most important parameters. In this paper there is analyzed the selection of the thermoelectric elements considering to its size and possibility to integrate it into human wearing clothes. There is totalized how many and what kind of elements are required for the elimination of the heat excess of 300 W from human body and where can be integrated such elements for the best efficiency and comfort.